Marcadores genéticos de risco para forte produção de biofilme em cepas clínicas de Staphylococcus aureus resistentes à meticilina e sua associação com o perfil clonal - Batistão, Deivid William da Fonseca (2014)
Methicillin-resistant Staphylococcus aureus (MRSA) is one of the major human pathogens worldwide and its epidemiology has been the focus of numerous single and multicenter surveillance studies over the past years. In this study, a phenotypic and genotypic approach were used to determine the factors that influence adherence and biofilm production of the most common MRSA SCCmec types, and its relationship with antimicrobial resistance, virulence genes and the genetic background of S. aureus isolates. The strains used in this study were selected from a collection of clinical MRSA strains recovered from patients hospitalized in the Teaching Hospital of the Federal University of Uberlandia, isolated from infections at various anatomical sites and evaluated for SCCmec type. Fifteen strains carrying different chromosomal cassettes were selected, five SCCmec II, five SCCmec III and five SCCmec IV, recovered predominantly from blood (67%), surgical site infections (27%) and pneumonia (6.0%). The SCCmec type, agr group and the presence of the virulence genes (bbp, clfA, icaA, icaD, fnbB, bap, sasC and IS256) were assessed by PCR. The genetic relationship between the isolates and a possible association with the ability to form biofilm were investigated by pulsed field gel electrophoresis (PFGE). The initial adhesion and biofilm formation were examined by quantitative assays. To evaluate the association between the hydrophobicity and the ability of MRSA cell to adhere to an unmodified polystyrene surface, the surface tension and hydrophobicity of the strains were measured by contact angle technique. There were association among the values of the electron acceptor parameter, the degree of hydrophobicity and adhesion ability. SCCmec III and IV strains were less hydrophilic, showed higher values of the electron acceptor parameter and adhered better than SCCmec II strains. The analysis of biofilm production showed that SCCmec III strains were characterized as strong biofilm producers; with the average biomass of biofilm from 0.53 ± 0.12 compared with 0.04 ± 0.04 those non-producers/weak producers (SCCmec II e IV). The analysis of this study showed five major pulsotypes according to the PFGE (A-E) with a large genomic diversity observed by the number of subtypes in each pulsotype. However, biofilm production was related to the dissemination of one specific PFGE clone (Clone C). The presence of the genes agrI, fnbB and IS256 in clinical MRSA SCCmec III strains, were considered as genetic risk markers for strong biofilm-formation by an icaindependent biofilm pathway. This study contributes for the understanding of biofilm production as a virulence factor potentially involved in the persistence and severity of infections caused by Staphylococcus aureus belonging to this genotype.